Pelatihan Communicative Interview in English Untuk Mempersiapkan Karir Di Dunia Kerja Bagi Siswa SMK Muhammadiyah Ponpes Jekulo Kudus - Atik Rokhayani; Aisyah Ririn Perwikasih Utari (Universitas Muria Kudus, 2020)
There are two things that SMK graduates can do after they graduate, namely entrepreneurship and looking for a job. The first choice looks very good and becomes the dream of every graduate, especially if they already have a mature plan and business capital. While the choice of number two can be made by graduates who really want to explore more experience in the field and then can continue to do it independently. In the midst of increasingly intense and fierce competition in the world of work, something that looks interesting and different from others is needed, especially when offering and demonstrating skills in front of targeted companies. One of them is during the interview. This is the final stage that can be done to seize the best impression from the company's Human Resources Development (HRD). The use of Indonesian may also be something that is very commonly used when interviewing. To attract the attention of employers, English-language interviews will be enough to show that the applicant's language knowledge is good enough to eventually be accepted into a company.